Colonization and Infection due to Multi-resistant Bacteria in Neonates: A Single Center Analysis - Haase, R.; Worlitzsch, D.; Schmidt, F.; Kulka, R.; Kekulé, A. S.; Körholz, D. (Klinische Pädiatrie, 2014)
In the last years the prevalence of multi-resistant pathogens (MRPs) has increased. Systemic infections remain important for neonatal morbidity and mortality.Neonates born between January 2011 and December 2012 and admitted to the neonatology before their tenth day of life were included into this retrospective analysis. Vancomycin-resistant Enterococci, Methicillin-resistant Staphylococcus aureus, Gram-negative bacilli with Extend Spectrum Beta Lactamase or AMP-C resistance were defined as multi-resistant pathogens (MRPs). MRP positive and negative patients were analyzed regarding clinical risk factors and the incidence of systemic infections.635 neonates were admitted during the analysis period. In 31 patients MRPs were detected. 2 patients developed MRP-associated infections. Both were discharged without long term health risks. Low gestational age and need for mechanical ventilation were risk factors for colonization with MRPs in the univariat analysis. The incidence density (per 1 000 patient days) for all MRE increased from 0.76 in 2011 to 3.51 in 2012. In contrast the sepsis rate remained stable (14.9% and 14.2%). 2 MRP colonization clusters were detected by routine microbiology swabs. Both could be controlled by appropriate hygienic measures.The prevalence of Gram-negative MRPs increased in neonates. Microbiological screening seems to be helpful for early detection of colonization and thus prevention of nosocomial infections with MRPs. Despite the increased attention towards the problems associated with multiresistant bacteria, there are still major efforts needed for prevention and early treatment of sepsis with non-resistant bacteria.
Keywords: multiresistant bacteria; neonate; colonization; neonatal infection